Developing Students' Communication Skills in English Lessons - Baxavedinovich, Allanyazov Marat (Innovative Technologica: Methodical Research Journal, 2024)
In modern society, there is a tendency to create a single global economic space, which entails an increase in the interconnections between people from different countries. This suggests that intercultural communication is reaching a completely new level, in which representatives of different countries are increasingly interacting with each other more closely.